Erosion of the Subsurface Salinity Maximum of the Loop Current Eddies From Glider Observations and a Numerical Model. Issue 7 (17th July 2020) - Sosa‐Gutiérrez, R.; Pallàs‐Sanz, E.; Jouanno, J.; Chaigneau, A.; Candela, J.; Tenreiro, M.
Abstract: The erosion of the subsurface salinity maximum, signature of the Caribbean Subtropical UnderWater (SUW), within the Loop Current Eddy (LCE) Poseidon (August 2016 to July 2017) in the Gulf of Mexico (GoM) and the formation of the Gulf Common Water (GCW) during its journey westward, was observed using glider data. Most of the dilution of the SUW high‐salinity core within Poseidon occurs during late autumn and winter associated with Northern winds and mixed‐layer deepening. The physical processes that contribute to salt dilution of the SUW inside the LCEs' core are investigated using a numerical regional model. The analysis of the salt budget in a long‐lasting numerical LCE and a composite analysis of sixteen LCEs reveal that the salinity trend is mostly explained by the vertical salinity diffusion. Cold and dry Northern winds during the first winter drive strong negative net heat fluxes that trigger turbulent flux of salt into the LCEs' thermostad and dilution of the SUW high‐salinity core below. The vertical salinity diffusion continues homogenizing the salinity in the upper ocean until the vertical gradient of salinity is negligible. As a result, SUW is transformed to precursor of GCW that is ultimately diffused to surrounding waters in the western GoM. Although the contribution of advection to the salinity trend above the isopycnal of 1, 026 kg m −3 is of second order, below is the most important process driving loss of salinity, presumably due to, eddy‐eddy interactions during LCEs' westward propagation and eddy pumping (upwelling) during the LCEs' decaying phase along the western slope. Plain Language Summary: This study shows that the vertical salinity diffusion (ZDF) is the main physical process that controls the erosion of the Caribbean Subtropical UnderWater high‐salinity core within the Loop Current Eddies during the first winter of their life cycles in the Gulf of Mexico. The ZDF during winter is associated with negative heat fluxes that are driven by thermal convection mixing through the passage of cold and dry fronts (Northerly winds). It is suggested that the formation of the Gulf Common Water is due to the progressive erosion of the high‐salinity core of the Loop Current Eddies during their journey to the west of the Gulf of Mexico. Key Points: The vertical structure of salinity is similar from one eddy to another, regardless of the detachment month from the LC The most important physical process that controls the salt budget in the LCEs' core is the vertical salinity diffusion The vertical salinity diffusion is driven by thermal convection due to cold and dry Northerly winds